Pengaruh Konsumsi Rokok, Tingkat Pendidikan, dan Pendapatan Terhadap Konsumsi Kalori di Provinsi Lampung: Penelitian - Umar Wafa Al-Haiban; Toto Gunarto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Calorie Calorie consumption is an important indicator in assessing household welfare and nutritional quality. Lampung Province is recorded as having the lowest average calorie consumption on the island of Sumatra, while simultaneously exhibiting the highest smoking prevalence in Indonesia. This condition indicates a distortion in household expenditure allocation, particularly due to cigarette consumption. This study aims to analyze the effects of cigarette consumption, income, and education level on household calorie consumption in Lampung Province. A quantitative approach is employed using district/city panel data in Lampung Province for the period 2018–2024. The analytical method applied is panel data regression, with the selection of the best estimation model conducted through the Chow test, Hausman test, and Lagrange Multiplier test. The results indicate that an increase in cigarette consumption of one thousand rupiah raises calorie consumption by 36.50 kilocalories, an increase in education level by one year increases calorie consumption by 154.34 kilocalories, and an increase in income of one thousand rupiah raises calorie consumption by 19.76 kilocalories. These findings suggest that improvements in income and education play a crucial role in enhancing household energy consumption. This study is expected to provide empirical evidence for the formulation of integrated cigarette control policies aimed at improving nutritional quality and educational attainment in Lampung Province.